Diagnostic study of fungal and bacterial pathogens that cause vaginal infection in women - Heba Hadid Rashed; Ibtihal Muiz Al-Hussaini; Ali H. Al-Marzoqi (Medical Journal of Babylon)
Abstract Background: Vaginal infection is an inflammation of the vagina that can result in discharge, itching, and pain. A specific kind of vaginal inflammation known as bacterial vaginosis is roughing on by an overabundance of naturally occurring bacteria in the vagina, which throws the body’s delicate equilibrium out of whack. Vaginal candidiasis is a fungal infection that affects the vagina and the vulva, the tissues at the vaginal opening, causing irritation, discharge, and severe itching. Objectives: Isolation, identification, and partial purification of bacteria and fungi that cause vaginal infection. Materials and Methods: In this study, 150 vaginal samples were collected from women aged 15–55 who did not have any chronic diseases in the city of Hilla, Iraq. Cultivation of samples of bacteria on MacConkey, mannitol salt, and Eosin-methylene blue culture media and fungi on potato dextrose agar medium and chromo agar for Candida and conducting diagnostic tests for them. Results: The samples were culture on different medium. Bacteria have a percentage (55.3%) and fungi percentage (54.7%). Types of bacteria that appeared are Escherichia coli 24.3%, Klebsiella 20%, and Staphylococcus aureus 55.7%. Fungi are Candida albicans 52.6%, Candida glabrata 23.7%, and Candida krusie 23.7% have all been identified as fungi in clinical cases. Biochemical tests were performed for each sample, whether bacteria or fungi and included an examination (indol, citrate, urease, catalase, oxidase, coagulase, and H2S). Conclusion: Through results appeared S. aureus papered was found to be more common than bacteria species and fungi in clinical cases. C. albicans was found to be more common than other Candida species.